Relationship between changes in activities to prevent disability due to the COVID-19 pandemic and mental status or life-related functions among community-dwelling older adults - Keita Nakagawa; Hungu Jung; Hitoshi Okamura; Tomoyuki Ishii; Shinya Ishii (Archives of Gerontology and Geriatrics Plus)
Background: Disability prevention is important for older adults and the society at large. Despite its relevance, factors associated with changes in disability prevention activities due to the COVID-19 pandemic remain unclear. This study aimed to investigate the extent to which the implementation of disability prevention activities has changed due to the COVID-19 pandemic among community-dwelling older adults, and to examine the relationship between these changes and mental status or life-related functions. Methods: This cross-sectional study used self-report questionnaires with a random sample of older adults in 10 locations. The mailing area was determined based on the regional characteristics and demographic changes. Participants were categorized into two groups: those who maintained their disability prevention activities and those who decreased such activities before and after the COVID-19 pandemic. Mental status and life-related functions were investigated using the Kihon Checklist. Results: Of the 263 participants included in the analysis, 89 (33.8 %) decreased their disability prevention activities before and after the COVID-19 pandemic. Factors associated with a decrease in disability prevention activities were identified as those with a higher number of depressive items on the Kihon Checklist (aOR = 0.788, 95 % CI: 0.637–0.947, p = 0.027) and those with a higher total number of disability prevention activities before the COVID-19 pandemic (aOR = 0.653, 95 % CI: 0.476–0.896, p = 0.008). Conclusion: These findings suggest the characteristics of older adults that require special attention when taking steps to support the continuation of disability prevention activities in future events such as the COVID-19 pandemic.